2016
DOI: 10.1007/s00192-016-3056-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the use of the IUGA/ICS classification system for prosthesis/graft complications in publications from 2011 to 2015

Abstract: Fourteen percent of the reports in the literature describing complications related to prosthesis/graft use in pelvic surgery utilize the category-time-site system. The system's limited and inconsistent use hinders the ability to draw conclusions useful for clinical practice. Effort should be directed toward improving appropriate usage or revising the system to increase its exposure in related publications. An improved system will better prepare pelvic surgeons for assessing future generations of prostheses/gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…This is not a surprising finding since only 14% of the reports in the medical literature describing complications related to prosthesis/ graft in pelvic surgery utilize this system. 23 Gowda et al 24 found that this classification has poor inter-observer reliability, highlighting its complex nature. Efforts should be directed toward developing an improved system to ensure a widespread application in clinical and research fields.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not a surprising finding since only 14% of the reports in the medical literature describing complications related to prosthesis/ graft in pelvic surgery utilize this system. 23 Gowda et al 24 found that this classification has poor inter-observer reliability, highlighting its complex nature. Efforts should be directed toward developing an improved system to ensure a widespread application in clinical and research fields.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the use of the IUGA/ICS classification system, we found that the vast majority of respondents do not use it or are not familiar with it. This is not a surprising finding since only 14% of the reports in the medical literature describing complications related to prosthesis/graft in pelvic surgery utilize this system . Gowda et al found that this classification has poor inter‐observer reliability, highlighting its complex nature.…”
Section: Discussionmentioning
confidence: 99%